2002
DOI: 10.1161/01.str.0000016327.74392.02
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Nervous Activity and Myocardial Damage Immediately After Subarachnoid Hemorrhage in a Unique Animal Model

Abstract: Background and Purpose-Obvious cardiac dysfunction, including ECG abnormalities and left ventricular asynergy, is known to develop after subarachnoid hemorrhage (SAH). To clarify the close relationship between myocardial damage and sympathetic nervous activity immediately after SAH, a novel experimental animal model was used. Methods-SAH was provoked by perforation of the basilar artery with the use of a microcatheter inserted through the femoral artery in 18 beagle dogs. Hemodynamic changes were recorded, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
117
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(127 citation statements)
references
References 39 publications
7
117
2
1
Order By: Relevance
“…Accordingly, the effects of SAH on parenchymal arteriolar constriction observed in the present study may be exacerbated by elevated blood pressures commonly observed in SAH (15,40). At this time, it is unclear how SAH causes enhanced pressure-dependent depolarization in parenchymal arterioles.…”
Section: Discussionmentioning
confidence: 53%
“…Accordingly, the effects of SAH on parenchymal arteriolar constriction observed in the present study may be exacerbated by elevated blood pressures commonly observed in SAH (15,40). At this time, it is unclear how SAH causes enhanced pressure-dependent depolarization in parenchymal arterioles.…”
Section: Discussionmentioning
confidence: 53%
“…Second, plasma catecholamine released into the systemic circulation after SAH is rapidly degraded and plasma levels decrease over time. 30,32 We attempted to reduce such time-related variability by our strict inclusion criteria (ie, including only patients in whom TTE and blood sample collection had been conducted within 48 hours of SAH onset). Nevertheless, the possibility that the difference in the timing of sample collection may have influenced measurement results cannot be denied.…”
Section: Discussionmentioning
confidence: 99%
“…Both experimental and clinical studies show that destruction or mechanical compression of the dorsal and solitary tract nuclei, which suppress sympathetic activity, leads to acute change in pulmonary vascular permeability and subsequent NPE. 13,22,23,30) A lesion in the solitary tract nucleus also seems to alter the secretion of brain natriuretic peptide, which may also be involved in the pathogenesis of NPE. 6,7) These findings may explain why poor-grade patients with ruptured posterior circulation aneurysm were significantly more likely to sustain NPE compared with anterior circulation aneurysm, as previously reported.…”
mentioning
confidence: 99%